(untitled) (UNWE Yearbook, 2024)
Many companies have fallen victim to fraud despite having an internal audit function. This paper studies and presents the role of internal audit in countering fraud in theoretical and practical terms. Based on studies of reputable organizations and authors, major trends in the current role of internal audit are highlighted. Opportunities are suggested and perspectives for internal audit are outlined to improve its effectiveness. The use of modern technologies, the application of complex approaches, achieving adequate competence, integrativeness and proactivity in anti-fraud processes are some of the opportunities that would increase the effectiveness and usefulness of internal audit